2012
DOI: 10.1371/journal.pone.0036616
|View full text |Cite
|
Sign up to set email alerts
|

Proton-Assisted Amino Acid Transporter PAT1 Complexes with Rag GTPases and Activates TORC1 on Late Endosomal and Lysosomal Membranes

Abstract: Mammalian Target of Rapamycin Complex 1 (mTORC1) is activated by growth factor-regulated phosphoinositide 3-kinase (PI3K)/Akt/Rheb signalling and extracellular amino acids (AAs) to promote growth and proliferation. These AAs induce translocation of mTOR to late endosomes and lysosomes (LELs), subsequent activation via mechanisms involving the presence of intralumenal AAs, and interaction between mTORC1 and a multiprotein assembly containing Rag GTPases and the heterotrimeric Ragulator complex. However, the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
141
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(150 citation statements)
references
References 71 publications
7
141
0
Order By: Relevance
“…For example, two members of the SCL38 family, proton-assisted amino acid transporter 1 (PAT1) and SLC38A9 have recently been found to directly interact with components of the Rag-Ragulator complex and to be involved in the regulation of mTORC1 activity. [22][23][24] Importantly, SLC38A9 was shown to interact with Rag-Ragulator in an amino acid-dependent manner, and to act as a positive regulator of mTORC1 activity, most likely independently of v-ATPase. The interaction between SLC38A9 and v-ATPase seems much less important than that of cystinosin and v-ATPase, suggesting that the mechanism of regulation of the mTORC1 pathway differs between these two amino acid transporters.…”
Section: Discussionmentioning
confidence: 99%
“…For example, two members of the SCL38 family, proton-assisted amino acid transporter 1 (PAT1) and SLC38A9 have recently been found to directly interact with components of the Rag-Ragulator complex and to be involved in the regulation of mTORC1 activity. [22][23][24] Importantly, SLC38A9 was shown to interact with Rag-Ragulator in an amino acid-dependent manner, and to act as a positive regulator of mTORC1 activity, most likely independently of v-ATPase. The interaction between SLC38A9 and v-ATPase seems much less important than that of cystinosin and v-ATPase, suggesting that the mechanism of regulation of the mTORC1 pathway differs between these two amino acid transporters.…”
Section: Discussionmentioning
confidence: 99%
“…PAT4 is a high-affinity, low-capacity electroneutral transporter of neutral amino acids (26). Baseline PAT expression is ubiquitous (15) and resides at the cell surface and intracellular membranes (endosomes, lysosomes) (27). Elevated PAT expressions have been linked to cell proliferation (24).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated PAT expressions have been linked to cell proliferation (24). Here, PATs function as part of an amino acid-sensing engine that drives activation of the mammalian target of rapamycin complex 1 (mTORC1) (27). Physiologically high PAT1/PAT2 expressions have been identified in the brain, pancreas, kidney, duodenum, and small intestine (24).…”
Section: Discussionmentioning
confidence: 99%
“…The Ragulator complex has been implicated in binding the Rag GTPase heterodimer to the lipid bilayer [33]. It was recently shown that the lysosomal membrane protein human member 9 of the solute carrier family 38 (SLC38A9), a physical and functional component of the amino acid sensing RagulatorRag GTPase complex, positively regulates the mTORC1 pathway [32,34].…”
Section: Signalling Pathways Regulating Autophagymentioning
confidence: 99%
“…It was recently shown that the lysosomal membrane protein human member 9 of the solute carrier family 38 (SLC38A9), a physical and functional component of the amino acid sensing RagulatorRag GTPase complex, positively regulates the mTORC1 pathway [32,34]. Additionally, the proton-assisted amino acid transporter 1 (PAT1) or SLC36A1 has been shown to be an essential modulator of amino acid-dependent mTORC1 activation [33]. Activation via this pathway leads to the translocation of mTORC1 to the lysosomal surface where it can be further activated by Rheb, stimulating the mTORC1 kinase activity [5].…”
Section: Signalling Pathways Regulating Autophagymentioning
confidence: 99%